Application Of Cultural Activities In Junior High School Students To Improve Creative Character And Responsibility: Penerapan Kegiatan Kultum Pada Siswa SMP Untuk Meningkatkan Karakter Kreatif Dan Bertanggung Jawab - pratiwi, nila; Aggy Pramana Gusman; Mutiana Pratiwi (KPN Kopertis X, 2025)
Various kinds of activities have been made by the school to instill character values ​​in students, which aim to create and strengthen individual characters in accordance with the morals and teachings of the Islamic religion. This research uses a qualitative descriptive research type. A cult is a way to convey good lectures and advice to others in a short and meaningful way. This cult in junior high school is in the form of guidance and counseling to identify students when they are doing activities that can create creativity and responsibility for these activities. This cult once a week on Friday morning, before the learning process begins. This Kultum program (seven-minute lecture) may need to take some time from 7 minutes to 30 minutes. The purpose of holding this student cult, among others, is to provide confidence for junior high school students to appear in public, inspire other students, and provide motivation and religious knowledge for other students. And as for the benefits of holding this student cult, among others, mental training and self-confidence, increasing religious insight, fostering an attitude of respect for fellow students, forming noble morals, improving mindsets, fostering creativity, and sense in students. Characters that are emphasized in this research focus more on character building. creativity, which is a form of personality to creates ideas that are developed and the ability to solve problems that exist within oneself.